The Model of Media Competence Formation of Future Workers in Film and Television Industries by Means of a Foreign Language - Kulikovskaya, Irina Eduardovna; Perekhoda, Alina Yurievna (International Review of Management and Marketing, 2015)
The article presents a theoretical analysis of research related to media education of students. The definition of media competence of students" as an integral characteristic of the future worker film and television, including the knowledge of the English language media culture; professional media skills and experience of creative activity in the media space by means of the English language; understanding of the professional values of media products has been formulated. One of the hypotheses of the study, which is related to the fact that it is possible to develop and implement a model for the development of media competence of students on the material of film, television, video English-speaking countries by involving them in creative activities on interpretation and analysis of screen media texts, with English language lessons on the material of media products has been presented. The model of formation of media competence of students by means of a foreign language includes the following components: professional metatext, the substantial-technological and diagnostic component. Keywords: media education, workers in film and television industries, media competence, professional metatext, learning a foreign language. JEL Classifications: I21; Z13